Efektivitas Standar Pelayanan Minimal Pada Dinas Pendidikan Daerah Provinsi Sulawesi Utara - Kalele, Jureine Valentin Debora; Tasik, Femmy; Kawung, Evelin (AGRI-SOSIOEKONOMI, 2023)
The purpose of this study was to find out more deeply how the effectiveness of Minimum Service Standards at the Regional Education Office of North Sulawesi Province. The research was conducted from March to August 2022. The selection of respondents was done intentionally. This research uses descriptive qualitative research design. Research informants used purposive sampling technique. The research focuses on the accuracy of program targets, program socialization, achievement of program objectives, and program monitoring. Data collection technique was carried out by means of observation, interviews, and documentation. Data analysis techniques in this study are data collection, data reduction, data presentation and conclusion drawing. The results showed that the Minimum Service Standards program has not run effectively and optimally. This is because this program does not run to the entire community and the process for verification with data control is not strict so that people still do not choose education facilitation from the government. In addition, the socialization process by the Regional Education Office of North Sulawesi Province did not reach the community, only to school administrators in the regions. The lack of control and supervision to influence the level of achievement of the fulfillment of students in each school in the region. There is no direct assistance from the field responsible for continuing to schools, especially those that are still included in remote areas so that this program does not show satisfactory results.